Implementasi Konsep Belajar dan Pembelajaran Perspektif Al-Quran di MI Nurul Muhajirin Kota Negara Kabupaten Lampung Utara - Mualimin, Mualimin (Lentera: Jurnal Ilmiah Kependidikan, 2015)
The emergence of quality educational institutions that are needed by the community in the midst of turmoil the world of education today. In this context, emerged the concept of a unified Islamic education, the concept of integrated education is assumed to be able to answer the problems of religious education and general education. Integrated Islamic education is expected to put the commitment to pave the way to build a quality education to seek to integrate the values ââof science and scientific religion common to expect mempu form of building strong and effective education. This study includes a descriptive study, the research describes the condition in the field with what it is. This type of research used in this research is the field (fild reseach) is the research by examining the facts and issues in the field. The research in the field is MI Nurul select Emigrants City State. The subjects were MI Nurul Emigrants City State. Data analysis technique is essentially qualitative procedures deductive-inductive logic. The process of data analysis begins by examining all the data collected from various sources, from interviews, observations that have been written in the field notes, personal documents, official documents, and so on. Curriculum developed by MI Nurul Muhajirin City State uses a combination of two curriculum curriculum namely general education curriculum nationally and religious education curriculum designed by MI Nurul Muhajirin City State Concept teaching and learning perspective of the Quran that diimplentasikan integrative manner students read over and over again, studying, reciting, memorizing and practicing the subject matter presented by the teacher. Teachers motivate students to straighten out the intent of the learning process and learning, and teachers are required to be exemplary, sincere, and patient in educating students.